2014
DOI: 10.1128/jcm.03561-13
|View full text |Cite
|
Sign up to set email alerts
|

Methylobacterium and Its Role in Health Care-Associated Infection

Abstract: bMethylobacterium species are a cause of health care-associated infection, including infections in immunocompromised hosts. The ability of Methylobacterium species to form biofilms and to develop resistance to high temperatures, drying, and disinfecting agents may explain the colonization of Methylobacterium in the hospital environment in, e.g., endoscopes. Due to its slow growth, it can be easily missed during microbiological surveillance of endoscope reprocessing. The purpose of this minireview is to present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 25 publications
1
63
0
1
Order By: Relevance
“…Many of the major bacterial groups observed in this dataset are commonly isolated from aquatic and terrestrial sources, and are therefore expected to be environmentally derived in both herbivorous and carnivorous species. Alicyclobacillus, Methylobacterium, Acinetobacter, and Agrobacterium represent some of the most abundant bacterial genera in our dataset, and all are common in soil and leaf surfaces (Vorholt, 2012; Kovaleva et al, 2014; Tianli et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Many of the major bacterial groups observed in this dataset are commonly isolated from aquatic and terrestrial sources, and are therefore expected to be environmentally derived in both herbivorous and carnivorous species. Alicyclobacillus, Methylobacterium, Acinetobacter, and Agrobacterium represent some of the most abundant bacterial genera in our dataset, and all are common in soil and leaf surfaces (Vorholt, 2012; Kovaleva et al, 2014; Tianli et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The decontamination procedures currently employed within sterile service departments (SSDs) for the reprocessing of reusable surgical instruments are very efficient against bacterial contamination although not always as effective in tissue protein decontamination or in bacterial decontamination of endoscope channels (Lipscomb et al 2006a;Kovaleva et al 2014;Peaper et al 2015). However, highly hydrophobic proteins such as prions may remain adsorbed to surgical stainless steel (SS) surfaces (Gibbs et al 1994;Lipscomb et al 2006b;Murdoch et al 2006;Herve et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that Methylobacterium strains isolated from bathrooms were tolerant to various stresses, including surfactants like benzalkonium chloride (BAC) (8,11). Some isolates even survived in 5.0% BAC after 5.0 min of exposure, indicating that cleaners need to act with more immediacy and versatility.…”
mentioning
confidence: 99%